ADVANTAGES AND DISADVANTAGES OF THE ONLINE LEARNING ENVIRONMENT: ASYNCHRONOUS AND SYNCHRONOUS LEARNING - Saydivaliyeva, Barno (Журнал иностранных языков и лингвистики, 2023)
The learning environment of the 21st century requires more than using technology to teach. True online learning environments use technology not only to provide anytime, anywhere access to information but also to allow some form of control over time, place, path, and/or pace. But even online learning environments are not individualized learning at your own pace.